TINGKAT LITERASI ILMIAH BUKU PEMBELAJARAN BIOLOGI KELAS XII - Amelia, Resty Ayu; Natalina, Mariani; Darmadi, Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims at describing the feasibility level of learning books according to the National Education Standards Agency (BSNP) and the scientific literacy level of class XII biology learning books based on 4 dimensions, namely science as a body of knowledge, science as a way of thinking, science as a way of investigation and science and its interactions with technology and society. This study uses a quantitative approach with the content analysis method. The sample in this study was the biology learning book for class XII by Irnaningtyas in the 2013 curriculum which was chosen by purposive sampling technique. The research data were obtained from the results of book feasibility and the level of scientific literacy by using book feasibility instruments according to the BSNP and a sheet of scientific literacy level analysis based on 4 dimensions. Stages of analysis were divided into 2 stages, namely the stage of book feasibility analysis and analysis of the level of scientific literacy of biology learning books. The data analysis was using descriptive statistical methods. The results of the data analysis show that the level of feasibility in the analyzed learning book has been declared feasible according to BSNP. At the level of scientific literacy, only the scientific dimension as a body of knowledge gets a good category. The results of this study can be used as material in the development of learning books based on the content of 4 dimensions of scientific literacy in balanced proportions. Key Words: Level of Literacy, Scientific Literacy, Learning Book, 2013 Curriculum